Complete 2020 AWS DevOps Bootcamp For Beginners (With ECS) - Wiesner, Thomas (Packt Publishing, 2020)
Develop the key skills needed to deploy containers to production using ECR/ECS, RDS, end-to-end CI/CD pipelines, and Route 53 services About This Video Get to grips with the fundamentals of DevOps and AWS Discover how to run an ECS cluster in a production-hosting environment Deploy a real-world Laravel PHP application with the help of an end-to-end workflow In Detail The rising popularity of AWS and DevOps is testimony to the fact that companies are able to build and deploy products speedily and reliably using AWS and DevOps practices. This course is packed with hands-on and practical labs which will help you to build real-world projects. The course begins with an introduction to DevOps and AWS. You'll then sign up for an AWS account, create Identity and Access Management (IAM) users, and discover how Elastic Cloud Compute (EC2) instances work. Going further, you'll find out how application load balancers and Auto Scaling groups help in scaling EC2 instances and explore AWS storage devices. As you advance, you'll create an Amazon virtual private cloud (VPC) and get an overview of Docker and containerization. You'll also work with Docker Compose and upload Docker images to Amazon Elastic Container Registry (ECR). Moving ahead, you'll delve into Amazon Elastic Container Service (ECS), continuous integration (CI), continuous delivery (CD), and continuous deployment. Finally, you'll work on a project to set up, configure, containerize, and deploy a Laravel PHP application. By the end of this course, you'll have gathered the skills needed to deploy containers to production using ECR and ECS.